Pop Up Book Learning Media to Increase Learning Interest of MTsS Alwasliyah Students Bangun Purba - Diyah Hoiriyah; Nurul Maulidia (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This article aims to increase students' interest in learning mathematics by using pop up book learning media. The research was conducted at MTsS Alwasliyah Bangun Purba class VII. The research method used is a descriptive qualitative method. The instruments in this study are observation sheets and questionnaires of students' interest in learning mathematics. The results of the study obtained that there was an increase in students' interest in learning after the learning process was carried out using pop-up book media.